The Role of Raden Adjeng Kartini Statue In The National Awakening Museum - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Benjamin, Donald; J.M.A, Valdero; Pratama, Reza Aditya (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The statue of R.A. Kartini in the National Awakening Museum plays an important role in visualizing the history of national awakening, especially the role of female figures in the struggle for Indonesian independence. The Kartini statue at the National Awakening Museum is a visualization of the figure of the emancipation fighter, which is manifested in the form of a chest-length sculpture. In addition, the role of women in the effort for Indonesian independence was very important, and figures such as Cut Nyak Dien, Raden Dewi Sartika, Nyi Ageng Serang, and Martha Christina Tiahahu also fought for Indonesian independence. The method carried out in this journal is descriptive qualitative.